BANK EFFICIENCY AND GOVERNANCE: EVIDENCE FROM JOINT VENTURE AND FOREIGN COMMERCIAL BANKS IN VIETNAM - Thao Nguyen; Thong Dao; Jeremy Cheah (Applied Finance Letters, 2023)
In this paper, we intend to examine the influence of national governance on the bank efficiency of joint venture and foreign commercial banks in Vietnam. Joint venture and foreign commercial banks have been instrumental in introducing new financial products to the Vietnamese market (e.g., mortgage services and medium-term certificates of deposit). At the same time, they have also penetrated the retail market through automobile and housing loans, and international credit card services.  We use the DEA double bootstrap method to develop a bank network function to evaluate bank efficiency. The findings from our random-effects model demonstrate that world governance indicators as proposed by the World Bank independently determine the bank efficiency of the joint venture and foreign commercial banks in Vietnam. There are important implications to be highlighted for policymakers and stakeholders of joint venture and foreign commercial banks and other types of banks in the banking industry elsewhere around the world.